The method for identifying of inaccuracy causes in turning machining center by processing a sample part - D. A. Blokhin; A. G. Koltsov; Yu. A. Blokhina; M. M. Lakman (Омский научный вестник)
The article discusses the issues of the processing method of a turning machining center for processing the accuracy of processing a sample part. The model of sample part with the smallest possible control surfaces processed by various shaping methods has been developed to detect the amount of machine errors, such as the accumulated error of the screw pitch, or the axial non-perpendicularity, or the misalignment of the X and Y drives. This allows you to get more complete information of the equipment accuracy. A test procedure is presented according to the results of measuring each surface of the sample part.